Lipid biomarker signatures as tracers for harmful cyanobacterial blooms in the Baltic Sea - Bauersachs, T.; Talbot, H.; Sidgwick, F.; Sivonen, K.; Schwark, Lorenz (Public Library of Science, 2017)
Â© 2017 Bauersachs et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. The recent proliferation of harmful cyanobacterial blooms (cyanoHABs) in the Baltic and other marginal seas poses a severe threat for the health of infested ecosystems as e.g. the massive export and decay of cyanobacterial biomass facilitates the spread of bottom water hypoxia. There is evidence that cyanoHABs occurred repeatedly in the Baltic Sea but knowledge of their spatiotemporal distribution and the cyanobacteria that contributed to them is limited. In this study, we examined representatives of the major bloom-forming heterocystous cyanobacteria (i.e. Aphanizomenon, Dolichospermum (formerly Anabaena) and Nodularia) to establish lipid fingerprints that allow tracking these environmentally important diazotrophs in the modern and past Baltic Sea. The distribution of normal and mid-chain branched alkanes, fatty acid methyl esters, bacteriohopanepolyols and heterocyst glycolipids permitted a clear chemotaxonomic separation of the different heterocystous cyanobacteria but also indicated a close phylogenetic relationship between representatives of the genera Aphanizomenon and Dolichospermum. Compared to the discontinuous nature of phytoplankton surveys studies, the distinct lipid profiles reported here will allow obtaining detailed spatiotemporal information on the frequency and intensity of Baltic Sea cyanoHABs as well as their community composition using the time-integrated biomarker signatures recorded in surface and subsurface sediments. As heterocystous cyanobacteria of the genera Aphanizomenon, Dolichospermum and Nodularia are generally known to form massive blooms in many brackish as well as lacustrine systems worldwide, the chemotaxonomic markers introduced in this study may allow investigating cyanoHABs in a great variety of contemporary environments from polar to tropical latitudes.